Development of Marketing Strategy and Financial Management In The Jamu Mulya Sari Abadi Herbal Medicine Group - Subarjo Subarjo; Widarta Widarta; Arita Witanti; Yetti Lutiyan Suprapto; Shadrina Hazmi; Rina Dwiarti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Dusun Watu VII RT 8 Argomulyo, Sedayu, Bantul geographical area is suitable for empon-empon farming. Empon-empon is the raw material for making jamu (herbal medicine). Most of the population of Dusun Watu also has competency in making herbal medicine and is involved in the herbal medicine production business, either as groups or individually. One of them is the Jamu Mulya Sari Abadigroup. Production of herbal medicine before the COVID-19 pandemic, which was absorbed by the asset market when nominalized, reached 15 million rupiahs. This number has decreased drastically to around 5-6 million Rupiah, during the COVID-19 pandemic. The numbers have started to increase post-COVID-19 pandemic, but are not yet significant and still far from pre-COVID-19numbers. The absence of online marketing and business financial management became the basis for the community service team to provide training and mentoring in managing MSME scale business finances and developing marketing strategies through digital marketing. The training and mentoringare aimed at increasing the capacity of the JamuMulya Sari Abadi herbal medicine group so that it is expected to be able to manage its business optimally, as well as the products could reach a wider market. In this way, it is expected to increase revenue, and for the future impact, the Jamu Mulya Sari Abadi business could grow and be sustainable.